Environmental activism and pro-environmental behavior in Serbia: determinants and relationships with subjective well-being - Popov, Boris; Zorić, Jovana; Bodroža, Bojana (Psihološka istraživanja, 2023)
Environmentally significant behaviors, such as pro-environmental behavior and environmental activism, have remained relatively ill-defined and poorly integrated to date. The relationship between environmental activism and subjective well-being is particularly unclear. Therefore, the aim of this research was to determine whether some socio-demographic characteristics, such as gender, age and level of education, predict pro-environmental behavior and environmental activism, as well as whether these behaviors have an effect on subjective well-being. A total of 354 respondents (222 female respondents; 62.7%) filled out the Environmental Responsibility Feelings Scale, the Ecological Behaviour Scale, and the Environmental Activism Scale. Path analysis revealed that older respondents and those with a higher level of education exhibit more pro-environmental behavior and environmental activism. The results also suggest that the feeling of responsibility towards the environment significantly predicts the level of environmental activism, but not pro-environmental behavior. Gender did not show a significant effect on either pro-environmental behavior or environmental activism. Finally, it was found that environmentally significant behaviors in this research are not related to subjective well-being. Possible explanations of the obtained results are offered, as well as guidelines for future research into these phenomena.